دور دارات المضخات الحرارية الانضغاطية العاملة على الماء كوسيط تبريد في حماية البيئة وتوفير الطاقة - ناعمة وجيه (Latakia University Journal -Engineering Sciences Series, 2019)
استخدم الماء منذ عشرات السنين كوسيط تبريد في الدارات الامتصاصية العاملة على مزيج بروميد اليثيوم والماء, ولكنه في دارات التبريد الانضغاطية البخارية غير معروف, لذلك تمت الدراسة في هذا البحث لدارات التبريد والمضخات الحرارية العاملة على الماء كوسيط تبريد. وخلصت الدراسة بأن هذه الدوارات تتميز بأن معامل الأداء الحراري εHp يزيد بحوالي 50% بالمقارنة مع معامل الأداء للمضخات الحرارية التقليدية العاملة على الفريونات, ومعامل الأداء التبريدي εc بحوالي 65%, بالإضافة إلى ذلك حماية البيئة من تخريب طبقة الأوزون وغازات CO2, حيث أن معامل تخريب طبقة الأوزون يساوي الصفر بالإضافة إلى معامل البيت الزجاجي أيضا يساوي الصفر. ولكن مساوئ هذه الدارات العاملة على الماء, الحد من درجات الغليان, والتي أصغرها بشكل نظري يساوي الصفر ولكن حالياً توجد وحدات تبريد تعمل عند t0=6C درجة حرارة غليان الماء و باستطاعات كبيرة تبلغ حتى 1MW. Decades ago water was applied in the absorption refrigerating processes with Bromid Lithium but water not Known as refrigerant in the compressing processes up till now. For that reason, a study has made in this research for heat pump and refrigerating processes with water as refrigerant The results of this research is : Thermodynamically left processes with water as refrigerant are in possession of 50percent higher heat coefficient of performance and 65 percent higher refrigerating coefficient of performance in comparison to application of conventional refrigerant (R12,R22). Anther advantages is the RODP(Relative Ozone Debatably Potential ) is zero and the Green House Effect (GHE=0) is zero also. But the disadvantages is the evaporating temperature (t0) is not lower than zero Theoretically (t0 = 0C0 ). Nowadays , there are processes with( t0 = 6C0) and refrigerating a achievement is 1000 KW